2023
DOI: 10.46852/0424-2513.2.2023.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Exploration of Traditional versus Improved Cultivation Practices vis-à-vis Return on Investment of Jute Production System in lower Gangetic Plain of India

Abstract: "In the current study, an effort has been conferred to estimate the comparative return value per one-rupee investment for jute cultivation with traditional and improved practices. The research was carried out in four villages of two selected blocks of Murshidabad district in West Bengal and cost concepts were used for the estimation of the return on investment. In this inquiry, all calculations were done as per the land unit of acre (1 acre = 0.406 ha or 3.03 bigha). There were 35.85% savings in case of hired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Lal et al 12 used exploratory factor analysis (EFA) and identified 4 types of broad impediments viz., environmental constraints, pecuniary constraints, policy constraints and miscellaneous impediments and ranked by using Garrett ranking technique. Similar in-depth study had been carried out by Sinha et al, 13 Popoola et al, 14 Bandhavya et al, 8 Lal et al 15 Reviewing the above studies, this paper uncovers various impediments perceived by farmers in the cyclone affected region of Odisha.…”
Section: Introductionsupporting
confidence: 67%
“…Lal et al 12 used exploratory factor analysis (EFA) and identified 4 types of broad impediments viz., environmental constraints, pecuniary constraints, policy constraints and miscellaneous impediments and ranked by using Garrett ranking technique. Similar in-depth study had been carried out by Sinha et al, 13 Popoola et al, 14 Bandhavya et al, 8 Lal et al 15 Reviewing the above studies, this paper uncovers various impediments perceived by farmers in the cyclone affected region of Odisha.…”
Section: Introductionsupporting
confidence: 67%